2016
DOI: 10.1042/bj20150828
|View full text |Cite
|
Sign up to set email alerts
|

Stoichiometry of the eIF2B complex is maintained by mutual stabilization of subunits

Abstract: The eukaryotic translation initiation factor eIF2B is a multi-subunit complex with a crucial role in the regulation of global protein synthesis in the cell. The complex comprises five subunits, termed α through ε in order of increasing size, arranged as a heterodecamer with two copies of each subunit. Regulation of the co-stoichiometric expression of the eIF2B subunits is crucial for the proper function and regulation of the eIF2B complex in cells. We have investigated the control of stoichiometric eIF2B compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 28 publications
2
36
0
Order By: Relevance
“…Since the proper function of eIF2B, a multi‐component complex, is sensitive to tight regulation of the co‐stoichiometric expression of its subunits (Wortham et al . ), a genetic rescue experiment by over‐expressing the WT eIF2B5 subunit is not an option. However, in view of the fact that the mouse model was generated by homologous recombination into the Eif2b5 gene locus of a fragment containing the desired point mutation (Geva et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the proper function of eIF2B, a multi‐component complex, is sensitive to tight regulation of the co‐stoichiometric expression of its subunits (Wortham et al . ), a genetic rescue experiment by over‐expressing the WT eIF2B5 subunit is not an option. However, in view of the fact that the mouse model was generated by homologous recombination into the Eif2b5 gene locus of a fragment containing the desired point mutation (Geva et al .…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of the cause-and-effect relationships between ER and mitochondria in VWM disease, this study clearly illuminates eIF2B, a master translation initiation factor, as a fine-tuner of integrated cellular protein synthesis as a result of its role as a coordinator of cytoplasmic and mitochondrial translation. Since the proper function of eIF2B, a multi-component complex, is sensitive to tight regulation of the co-stoichiometric expression of its subunits (Wortham et al 2016), a genetic rescue experiment by over-expressing the WT eIF2B5 subunit is not an option. However, in view of the fact that the mouse model was generated by homologous recombination into the Eif2b5 gene locus of a fragment containing the desired point mutation (Geva et al 2010), offtarget genetic effects are not expected.…”
Section: Discussionmentioning
confidence: 99%
“…This complex may not have been previously identified as characterisation of mammalian eIF2B subcomplexes has not been carried out under stress conditions (Wortham et al, 2014). However previous work has demonstrated that the knockdown of eIF2Bβ leads to a reduction in the expression of all eIF2B subunits with eIF2Bδ suffering the greatest reduction (Wortham et al, 2016). These data show that eIF2Bβ is required to stabilise the expression of eIF2Bδ and as these subunits are known to heterodimerise it could be expected that eIF2Bβ stabilises eIF2Bδ through binding to it.…”
Section: Discussionmentioning
confidence: 79%
“…It has been proposed that first a heterodimer of eIF2Bβ and eIF2Bδ bind the catalytic heterodimer, through interactions between eIF2Bβ and eIF2Bɛ, and eIF2Bδ and eIF2Bγ to form a tetrameric subcomplex (Figure 1.9). The decamer is completed through the joining of two tetrameric complexes stabilised by a homodimer of eIF2Bα ( Figure 1.9) (Wortham and Proud, 2015;Wortham et al, 2016). Studies in yeast first revealed that the eIF2B regulatory subunits share high sequence homology, particularly in their C terminal domains (Figure 1.10) (Bushman et al, 1993;Paddon et al, 1989) which are highly conserved from yeast to mammalian cells (Price et al, 1996).…”
Section: Eif2b Structural Arrangementmentioning
confidence: 99%
See 1 more Smart Citation